Study Of Factors Determining English Language Ability Students Of High School Nutrition Study Program Nabire Persada Health Science - Syarifah Adriana; Purnama Ramadhani; Enjelika K Demetouw (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
English language skills are very important for students to support academic tasks and to support their future careers. English language skills include listening, speaking, reading and writing skills. The purpose of this study was to determine the determining factors of English language skills of students in the Nutrition Science study program at the Persada Nabire Health Sciences College (STIKes). The type of research used is descriptive research with a qualitative approach. Data collection techniques used are interviews and documentation. The results of this study indicate that in general the determining factors of English language skills of students of the Nutrition Study Program of STIKes Persada Nabire include 4 factors, including: Listening Ability, in this case students have a low vocabulary, Speaking Ability, in this case what affects students' speaking ability is the students' anxiety about mistakes in speaking English and lack of mastery of English grammar, Reading Ability, factors that affect students are reading motivation and low vocabulary and lack of mastery of grammar, Writing Ability, factors that affect students are low interest and lack of support from the environment around students.